Recognizing and Managing Allergic Contact Dermatitis: Focus on Major Allergens - Fonacier, Luz; Uter, Wolfgang; Johansen, Jeanne Duus (The Journal of Allergy and Clinical Immunology: In Practice, 2024)
Patch testing is the reference standard for the diagnosis of allergic contact dermatitis. Identification and avoidance of culprit allergens are essential in the treatment of this disease. Each year, new allergens are identified as emerging or important. The authors discuss allergens that are common, enduring, emergent, incompletely recognized, and controversial for the practicing allergist and dermatologist. This Clinical Management Review will encompass a review of fragrances, preservatives, rubber, acrylates, metals, and medications; their common sources of exposure; controversies in diagnosis and patch testing; management and how to avoid those allergens. This review will also include practical aspects of diagnosis and management and will provide resources that can be used as guidance for physicians and patients on nickel, methylchloroisothiazolinone/methylisothiazolinone, and fragrance, the most common allergens positive on patch testing.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Allergic contact dermatitis; Contact dermatitis; Fragrance allergy; Irritant contact dermatitis; Patch testing; Preservatives; Resins; Rubber; Systemic allergic dermatitis